Modelling potential hydrological impact of abandoned underground mines in the Monday Creek Watershed, Ohio. Issue 25 (14th August 2012) - Wan, Rongrong; Liu, Desheng; Munroe, Darla K.; Cai, Shanshan
Abstract Abandoned underground mines (AUM) have caused dramatic environmental effects that are closely linked to regional sustainability. This paper explores the potential hydrological impact of AUM in the Monday Creek Watershed, a typically mined area in Appalachian region, using the Soil and Water Assessment Tool (SWAT 2005) model and Sequential Uncertainty Fitting (SUFI‐2), calibrated at both the global and local scales. The locally calibrated model better incorporates those key parameters relevant to AUM for specific sub‐basins and hydrologic response units. Data from the years 2003–2004 were used for calibration and 2005–2006 for validation. The results were quite satisfactory; both the coefficient of determination (R2) and the Nash–Sutcliffe efficiency statistic were over 0.80. The potential influences of AUM were assessed by modelling an alternative scenario assuming no AUM for the period 2003–2009. Results show that the hydrological process of lateral subsurface flow plays a dominant role in linking AUM to overall watershed hydrology. The potential hydrological impact of AUM is an increased annual lateral flow of 82.1%, and a decrease in annual surface flow by 15%, leading to an increase of 16.9% in annual water yield for the Monday Creek Watershed. The seasonal fluctuation of water yield has a similar trend to lateral flow, decreasing from March to August and increasing from August to January. Higher volume, higher flow peaks and higher recession constants characterized the hydrograph of daily streamflow from AUM. The results indicate that more emphasis should be put on lateral flow for further study of acid mine drainage and flooding control in those watersheds with AUM. Copyright © 2012 John Wiley & Sons, Ltd.